Globalization and investment opportunities - Arayssi, Mahmoud (2016)
This study builds on the MBA project work of one of the authors, Hanin A. Smahta, and the supervisory work of the first two authors. All authors were affiliated with the Suliman S. Olayan School of Business at the American University of Beirut at the time this research was originally conducted. The authors acknowledge the financial support of the American University of Beirut Research Board (URB) for funding data collection.